Suatu Kajian Literatur Aplikasi Radio Frequency Identification Dalam Bidang Pertanian - Wenny Marthiana; Nizwardi Jalinus (invotek, 2018)
One type of information system that is currently experiencing rapid development is RFID (Radio Frequency Identification). The system is used to provide high flexibility, easy to use, and is highly suited to activities that require automation. This system has also been used to replace the Barcode system function which is considered less flexible especially in the case of tracerability. This paper aims to explore the potential application of RFID in agriculture, both in technological developments, what applications can be used with RFID, constraints and Prospects. This is to assist in directing the agricultural sector in accordance with revolution 4.0, in order for agriculture in the small area primarily, able to compete in globalization. The method used is a review of the research journal in connection with RFID, and its application in the World of Agriculture. Of the 100 Journals downloaded, only about 53 Journals are in line with the purpose of this review. The source of JUrnal is. Google Scholar, World Web Science (WWS), Science Direct and other open access journals. The majority of research is obtained through the search method